A Critical Analysis of the Inconsistencies in Amina Wadud Gender Equality Movement in the Islamic World - Salman Alfarisi; M. Khairul Arwani (Hakamain: Journal of Sharia and Law Studies, 2024)
Gender equality has long been a topic of discussion and debate. Amina Wadud, a pioneer of the gender equality movement, is controversial for initiating actions unprecedented for women. The author chooses Amina Wadud because she took unprecedented steps: becoming an imam for prayer and later a Khatib interpreting the Quran, deviating from the author's prior understanding. The issues examined include how Amina Wadud's equality movement emerged, why she initiated it, and the problems of the equality movement analyzed by her. This fieldwork involves experts researching gender issues and uses descriptive qualitative data, gathering words from observed individuals and actors. Information comes from primary and secondary sources, including Amina Wadud's books, The Qur'an and Women: Rereading the Sacred Text from a Woman's Perspective and Inside The Gender Jihad: Women's Reform in Islam, using the Maslaha approach. The analytical method is descriptive. The study shows that the movement, part of a series of worship activities, fundamentally contradicts the concept of Maqasid Sharia due to its potential to cause societal harm, distorting public perception of services rendered. Amina Wadud's thoughts in the present era are inadequate and irrelevant because her movement is local, focusing on defending religious freedom. As the movement spreads, gaps will emerge in areas where religious freedom is not respected. Inconsistency and insignificance of Amina Wadud's movement in modern times stem from numerous criticisms and rejections from Muslims and scholars. Her movement cannot be implemented in the general public, where the majority of Muslims are already highly intellectual.